Immediate loading in partially edentulous patients with fixed implant-supported restorations cases report - Wang, Shuang; Duan, Siyi; Chen, Rui; Wang, Zijian; Tang, Yulong (Frontiers in Oral Health, 2024)
Objectives This article reports on four rare cases involving multiple trauma-induced adjacent missing anterior teeth in the maxillary or mandibular region. These cases were successfully treated using a 4-axial implant-based alternative insert and an immediate loading protocol. Material and methods This series of cases was summarized by retrospective study that 4 patients who received a total of 20 immediately loaded implants. These patients had suffered from trauma-induced loss of 8–9 adjacent anterior teeth. The 4-axial-implants were inserted with the assistance of digital pioneer drill guides. The surgical procedure involved alveolar bone trimming or ultrasonic osteotomy, eliminating the need for traditional large-area bone augmentation. Pre- and post-operative CBCT was matched using DTX Studio Implant software, the deviation of implant between actual position and preoperative design was measured and compared using SPSS software package. Results The average follow-up duration 48 months after implant prostheses, the cumulative retention rate of the implants was 100%, the marginal bone loss averaged 0.53 mm (SD 0.15 mm), and buccal plate bone loss averaged 0.62 mm (SD 0.41 mm). Conclusions This retrospective clinical report demonstrates the successful treatment of several patients with multiple adjacent maxillary or mandibular anterior teeth using four implant-supported screws to fix the frame and employing immediate loading. The approach resulted in long-term stable clinical outcomes. Moreover, the method not only shortens the period of edentulism but also facilitates easy disassembly, maintenance, and cleaning. Consequently, it emerges as a highly favorable clinical option for patients suffering from extensive tooth loss.